Targeting IGF1R pathway in cancer with microRNAs: How close are we?. Issue 3 (4th March 2018) - Kumar, Arathy S.; Rayala, Suresh K.; Venkatraman, Ganesh
ABSTRACT: Cancer of the head and neck are the most common cancers in India and account for 30% of all cancers. At molecular level, it could be attributed to the overexpression of growth factors like IGF1-R, EGFR, VEGF-R and deregulation of cell cycle regulators and tumor suppressors. IGF1-R is an emerging target in head and neck cancer treatment, because of its reported role in tumor development, progression and metastasis. IGF1R targeted agents are in advanced stages of clinical development. Nevertheless, these agents suffer from several disadvantages including acquired resistance and toxic side effects. Hence there is a need for developing newer agents targeting not only the receptor but also its downstream signaling. miRNAs are considered as master regulators of gene expression of multiple genes and has been widely reported to be a promising therapeutic strategy. This review discusses the present status of research in both these arenas and emphasizes the role of miRNA as a promising agent for biologic therapy.